Hexagonal obstacle drills enhance explosive power and agility in martial arts athletes / Muhamad Syafiq ... [et al.]. - Syafiq, Muhamad; Linoby, Adam; Sazali, Razif; Md Yusoff, Yusandra; Haziq, Amrun; Zulqarnain, Muhammad (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the effects of Hexagon Obstacle Drills (HOD) on explosive power and agility among martial arts student-athletes. Addressing gaps in combat sports research, it explores HOD’s potential to enhance lateral movement, agility, and power development, offering tailored, evidence-based training insights [1]. This experimental study employed pre- and post-tests with 20 martial arts student-athletes divided into control and experimental groups. The HOD was implemented with intensity and complexity tailored to participants. Explosive power and agility were measured using Vertical Jump and T-Tests, respectively. Data were analyzed using independent T-tests to evaluate HOD’s effectiveness on martial arts performance [2].